2012
DOI: 10.1590/s1517-83822012000400041
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of endophytic bacteria isolated from the leaves of the common bean (Phaseolus vulgaris)

Abstract: The common bean is one of the most important legumes in the human diet, but little is known about the endophytic bacteria associated with the leaves of this plant. The objective of this study was to characterize the culturable endophytic bacteria of common bean (Phaseolus vulgaris) leaves from three different cultivars (Vermelhinho, Talismã, and Ouro Negro) grown under the same field conditions. The density of endophytic populations varied from 4.5 x 10 2 to 2.8 x 10 3 CFU g The isolates from the Talismã culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(80 citation statements)
references
References 19 publications
4
72
1
3
Order By: Relevance
“…The fern, E. arvense (Figure 1), was collected from three different locations at the campus of Yeungnam University in 2014 (Gyeongsan, Republic of Korea), after which the endophytic bacteria were isolated by standard isolation protocol 38 . Briefly, 2 grams of the leaves, stems and roots of E. arvense were washed with running tap water, sterilized with 70% ethanol for 60 sec, 2% sodium hypochlorite for 90 sec and 100% ethanol for 30 sec, consecutively, and then washed five times with sterile ddH 2 O.…”
Section: Isolation Of Endophytic Bacteriamentioning
confidence: 99%
“…The fern, E. arvense (Figure 1), was collected from three different locations at the campus of Yeungnam University in 2014 (Gyeongsan, Republic of Korea), after which the endophytic bacteria were isolated by standard isolation protocol 38 . Briefly, 2 grams of the leaves, stems and roots of E. arvense were washed with running tap water, sterilized with 70% ethanol for 60 sec, 2% sodium hypochlorite for 90 sec and 100% ethanol for 30 sec, consecutively, and then washed five times with sterile ddH 2 O.…”
Section: Isolation Of Endophytic Bacteriamentioning
confidence: 99%
“…In Brazil, biotechnological research has targeted the diversity of microorganisms because of the potential for discovery of new bioactive compounds or bioprocesses (Schulz and Boyle, 2005;de Oliveira Costa et al, 2012;García et al, 2012b;Rhoden et al, 2012;Miguel et al, 2013;Polonio et al, 2015). Studies on microbiota associated with plants are important to understand and predict the spatial distribution of microbial communities and the ecosystem responses to global climate change (Singh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Rhoden et al (2015) identified 16 endophytic bacteria living on leaves of Trichilia elegans (Meliaceae), using sequencing and phylogenetic analyses. Several studies have isolated and identified endophytic bacteria of medicinal plants with the 16S rRNA gene used as a tool in molecular identification (Compant et al, 2010;de Oliveira Costa et al, 2012;Miguel et al, 2013;Castro et al, 2014;Rhoden et al, 2015).…”
Section: Taxonomic Purposesmentioning
confidence: 99%